Clinical characterisation and long-term prognosis of women with Brugada syndrome. Issue 6 (6th January 2016) - Sieira, Juan; Conte, Giulio; Ciconte, Giuseppe; de Asmundis, Carlo; Chierchia, Gian-Battista; Baltogiannis, Giannis; Di Giovanni, Giacomo; Saitoh, Yukio; Irfan, Ghazala; Casado-Arroyo, Ruben; Juliá, Justo; La Meir, Mark; et al.
Abstract : Objectives: Brugada syndrome (BS) in women is considered an infrequent condition with a more favourable prognosis than in men. Nevertheless, arrhythmic events and sudden cardiac death (SCD) also occur in this population. Long-term follow-up data of this group are sparse. The purpose of the present study was to investigate the clinical characteristics and long-term prognosis of women with BS. Methods: A consecutive cohort of 228 women presenting with spontaneous or drug-induced Brugada type I ECG at our institution were included and compared with 314 men with the same diagnosis. Results: Mean age was 41.5±17.3 years. Clinical presentation was SCD in 6 (2.6%), syncope in 51 (22.4%) and the remaining 171 (75.0%) were asymptomatic. As compared with men, spontaneous type I ECG was less common (7.9% vs 23.2%, p<0.01) and less ventricular arrhythmias were induced during programmed electrical stimulation (5.5% vs 22.3%, p<0.01). An implantable cardioverter defibrillator (ICD) was implanted in 64 women (28.1%). During a mean follow-up of 73.2±56.2 months, seven patients developed arrhythmic events, constituting an event rate of 0.7% per year (as compared with 1.9% per year in men, p=0.02). Presentation as SCD or sinus node dysfunction (SND) was risk factor significantly associated with arrhythmic events (hazard risk (HR) 25.4 and 9.1). Conclusion: BS is common in women, representing 42% of patients in our database. Clinical presentation is less severe than men, with more asymptomatic status and less spontaneous type I ECG and prognosis is more favourable, with an event rate of 0.7% year. However, women with SCD or previous SND are at higher risk of arrhythmic events.